DIAGNOSIS AND TREATMENT OF HYPERTHYROIDISM IN PREGNANCY: A REVIEW (Vietnam Journal of Community Medicine, 2026)
Objectives: This narrative review aims to evaluate the prevalence, clinical and laboratory characteristics, and management outcomes of hyperthyroidism in pregnant women.Method: A narrative review.Results: The prevalence of hyperthyroidism in pregnancy ranges from 3.93-23.60%, with the subclinical form being overwhelmingly predominant (78.95-90.48%). Clinically, tachycardia (OR up to 14.50) and palpitations are the most highly valued predictive indicators. Regarding laboratory findings, a suppressed TSH (< 0.1 mIU/L) combined with FT4 is the core diagnostic criterion, which must strictly be cross-referenced with trimester-specific reference intervals to avoid false-positive results. Uncontrolled hyperthyroidism significantly increases the risks of preterm birth (up to 46.7%), preeclampsia, and placental abruption. Intervention with antithyroid drugs is the primary therapeutic approach, utilizing a flexible strategy: prioritizing Propylthiouracil in the first trimester to prevent the risk of congenital anomalies (which can reach 13.2% with early Methimazole exposure) and switching to Methimazole in later stages. With optimal management, 85.6-89.0% of affected pregnancies can progress safely without severe complications.Conclusion: Hyperthyroidism in pregnancy largely progresses silently but carries severe obstetric consequences. Early screening of high-risk groups, accurate diagnosis using gestational age-specific TSH/FT4 reference ranges, and a flexible antithyroid drugs treatment strategy play a pivotal role in safeguarding maternal and fetal health.
Keywords: Hyperthyroidism in pregnancy, subclinical hyperthyroidism, antithyroid drugs (ATD), Graves’ disease, obstetric outcomes.